Effects of different drying rates on shrinkage characteristics of a residual soil and soil mixtures - Rahardjo, Harianto (2011)
This paper presents the experimental results of shrinkage tests using small cylindrical specimens. The shrinkage tests were performed to study the shrinkage characteristics of a residual soil and mixtures of residual soil and fine sand under three different drying rates. Small cylindrical specimens were dried under ambient conditions, under an accelerated evaporation using a fan, and under an accelerated evaporation using a lamp. The shrinkage curves of the soils were obtained by measuring the dimensions and the mass of the specimens periodically. The results of the experiments showed that the rates of changes in void ratio and degree of saturation of the soils were highly affected by the evaporation rates. However, the shrinkage curves of the soils, which is a plot of void ratio (e) versus water content (i.e., w · Gs, which is the product of gravimetric water content and specific gravity), was not affected by the drying rates. An identical shrinkage curve was obtained for the same soil under different drying rates. Similarly, the relationship between void ratio and matric suction for the same soil under different drying rates was also identical. It can be concluded that void ratio of the investigated residual soil and soil mixtures is a unique function of matric suction in the soil during drying process under zero net confining pressure.